Rachunkowość publicznej szkoły wyższej podstawowym źródłem informacji systemu controllingu - Krawiec, Magdalena (Accounting of Public Academy as a Basic Source of Controlling System Information, 2005)
The main aim of this article is to present relations between accounting system and controlling in public academy. An accounting system is considered as a basic source of information for controlling. An academy is described as a big and heterogeneous organization where controlling should be put into practice.(original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1085, s. 261-267